2013
DOI: 10.4047/jap.2013.5.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofilm formation, and biocorrosion on denture base fractures

Abstract: PURPOSEThe aim of this study was to investigate the destructive effects of biofilm formation and/or biocorrosive activity of 6 different oral microorganisms.MATERIALS AND METHODSThree different heat polymerized acrylic resins (Ivocap Plus, Lucitone 550, QC 20) were used to prepare three different types of samples. Type "A" samples with "V" type notch was used to measure the fracture strength, "B" type to evaluate the surfaces with scanning electron microscopy and "C" type for quantitative biofilm assay. Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…4 The material itself may become weakened. 8 The oral cavity is the most microbially polluted environment in the human body, such that more than 600 different species of bacteria and over 100 million bacterial cells may be recovered in every milliliter of saliva. 9 A fraction of this number is potential pathogens or existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…4 The material itself may become weakened. 8 The oral cavity is the most microbially polluted environment in the human body, such that more than 600 different species of bacteria and over 100 million bacterial cells may be recovered in every milliliter of saliva. 9 A fraction of this number is potential pathogens or existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…Huh et al and Hahnel et al reported that significantly higher number of Candida albicans was observed on roughened than on smooth surfaces [22,28]. Denture base cracks may become to be one of the best sites for microorganism propagation and provides protection from shear forces, even during denture cleaning [29,30]. The second step in DS is adherence of Candida albicans to host epithelial cells is a critical first step in the infection process [6][7][8]23,[29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Denture base cracks may become to be one of the best sites for microorganism propagation and provides protection from shear forces, even during denture cleaning [29,30]. The second step in DS is adherence of Candida albicans to host epithelial cells is a critical first step in the infection process [6][7][8]23,[29][30][31][32][33]. It is essential for both colonization and subsequent induction of mucosal disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite its obvious suitability as a denture base material 2,3 , PMMA is also susceptible to deterioration 4 , surface roughness following fatigue, microbial adherence [5][6][7] and colonisation by bacteria due to water absorption 1 . However, despite its obvious suitability as a denture base material 2,3 , PMMA is also susceptible to deterioration 4 , surface roughness following fatigue, microbial adherence [5][6][7] and colonisation by bacteria due to water absorption 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymethyl methacrylate (PMMA) resin has long been used as a denture base material 1 , because of its hardness and rigidity under masticatory pressure, ease of handling, good aesthetics and low price. However, despite its obvious suitability as a denture base material 2,3 , PMMA is also susceptible to deterioration 4 , surface roughness following fatigue, microbial adherence [5][6][7] and colonisation by bacteria due to water absorption 1 .…”
Section: Introductionmentioning
confidence: 99%